PREPARATION AND STUDY OF AMOXICILLIN SELECTIVE ELECTRODES AND THEIR APPLICATION WITH DERIVATIVE SPECTROPHOTOMETER IN PHARMACEUTICAL DRUGS - Al-Saidi, Khaleda H; Nassory, Nabil S; Maki, Shahbaz A (Al-Nahrain Journal of Science, 2009)
Amoxicillin trihydrate selective electrodes were prepared based on amoxicillin-phosphotungstate (Amox-PT) as an active sensor with different plasticizers, di-butyl phosphate (DBP), di-butyl phthalate (DBPH), di-octyl phthalate (DOPH), tri-butyl phosphate (TBP) and o-nitro phenyl octyl ether (NPOE) in PVC matrix membranes. The study was carried out to investigate the electrode parameters, effect of pH, selectivity and UV-derivative spectrophotometer technique. Internal filling solution of 10-3 M + 10-3 M NaCl was used to fill the electrodes. The best electrode was based on DBP plasticizer which gave a slope 58.7 mV/decade and detection limit of 2 x 10-6 M displayed good stability and reproducibility. The electrode was used to determine the amoxicillin in oral suspension and capsules. The results were compared with UV-derivative spectrophotometer technique and the recovery for the drugs obtained by second derivative are quite comparable with the recovery obtained by amoxicillin electrodes.